A study of the developmental history of skills resulting from changes in the bar change elements of the uneven bars - Murayama, D. (Japan Journal of Physical Education, Health and Sport Sciences, 2022)
Artistic gymnastics involves a huge number of elements. In order to plan training for the future, it is necessary to have a grasp of trends and developments for each apparatus and identify techniques that are worth passing on (Sano and Watanabe, 2019b). The evolution of elements and techniques for uneven bars (UB) up to around 1970 was described in Coaching of Artistic Gymnastics (Kaneko, 1974). However, the historical transition of elements and techniques that has occurred since then has not yet been thoroughly analyzed. In this study, through an analysis of trends in the historical development of elements and techniques related to UB, we clarified the factors associated with the development of UB elements with the aim of developing a systematic theory of gymnastics elements. We collected and organized historical data on UB, including rules, video materials, and research materials. The study was carried out using the method of historical research on sports technology adopted by Kishino (1972). From the results of the survey, we were able to grasp the timing and tendencies of rapid technological developments in UB, and searched for items that had had the most significant impact. The results of this research are summarized as follows. 1. The period from the introduction of the UB apparatus up to 1974 was characterized by the development of original morphology, and the concept of "flow-oriented exercise" was adopted and developed. 2. From 1975 to 1992, the adoption of the giant backward swing led to an increase in the distance between the bars, which greatly changed the developmental direction of the technique. In this era, "pursuit of the terminal phase" evolved. 3. From 1993 to 2021, "high difficulty orientation" evolved. Also, during this period, revision of the rules promoted developments designed to make existing structures more complex, and the occurrence of original morphology decreased. As of 2021, it can be said that changes in the elements of UB have tended to complicate the structure of the technique. In the future, it may be effective to formulate rules that place high value on new techniques that are considered to be creative forms.